Unemployment and psychological distress among graduates : a longitudinal study - Schaufeli, Wilmar B. [Verfasser]; Yperen, Nico W. Van [Verfasser] (My University, 1992)
"A longitudinal study which addresses the relationship between unemployment and psychological distress in Dutch technical college graduates is presented. Two samples were studied: sample 1 (N=635) consisted of students leaving technical college and sample 2 (N = 487) consisted of technical college graduates who had been unemployed for more than one year. In contrast to the results of many recent published studies, unemployment was only found to be asociated with psychological distress among those unemployed for more than two years. Males and females were not found to react differently to unemployment. Less psychologically distressed graduates were more likely to become employed than more distressed graduates, and the mean level of psychological distress decreased significantly over time for both employed and unemployed technical graduates. Individual vulnerability explained about twice as much variance in psychological distress of these respondents compared with changes in their employment status. Furthermore, this study indicates the importance of taking into account group-specific aspects (i.e. level of education) as well as the (Dutch) structural and cultural context in understanding the consequences of unemployment." (author's abstract) ((en)) Der Beitrag berichtet von einer in den Niederlanden durchgeführten Längsschnittstudie zu den psychischen Folgen von Arbeitslosigkeit bei den Absolventen eines technischen Colleges. Stress wurde nur bei denjenigen gefunden, die mehr als zwei Jahre arbeitslos waren. Bei Männern und Frauen wurden keine unterschiedlichen Reaktionsweisen festgestellt. (IAB)
Arbeitslosigkeit und psychologische Not unter Schulabsolventen - Eine Längsschnittstudie
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; S 3.1.2.3 Fachschule (Technikerschule); G 2.3 Wandel von Arbeit & Wirtschaft; Hochschule; Absolvent; Technische Hochschule; Arbeitslosigkeit; Auswirkung; Psychische Faktoren; Dauer; Geschlechtsspezifische Faktoren; Stress; Quantitative Angaben